A High Q-factor, Easy-to-use, Broadband Ce:LiCAF Laser Cavity Based on Total Internal Reflection - Ren, Arita; Melvin John F, Empizo; Yuki, Minami; Mui, Luong Viet; Takaya, Taniguchi; Kohei, Yamanoi; Toshihiko, Shimizu; Nobuhiko, Sarukura; Marilou Cadatal, Raduban; Duong, Pham Van; Tu, Nguyen Xuan; Minh, Pham Hong (Communications in Physics, 2017)
We report a design of a cerium-doped lithium calcium hexafluoro aluminumate (Ce:LiCaAlF\(_{6}\), Ce:LiCAF) laser resonator based on total internal reflection (TIR). This TIR configuration is established by placing the Ce:LiCAF crystal between two calcium fluoride (CaF\(_{2}\)) Pellin-Broca prisms. The laser resonator exhibits a 289-nm emission with 3.5-nm spectral linewidth and 4.4-ns pulse duration. Results show that the present configuration can be a high Q-factor, easy-to-use, broadband prism resonator suitable as a laser oscillator not only in the ultraviolet (UV) region but also down to vacuum ultraviolet (VUV) wavelengths where alignment is restricted to vacuum environments.